2015
DOI: 10.5860/lrts.59n4.172
|View full text |Cite
|
Sign up to set email alerts
|

E-book Use and Value in the Humanities: Scholars’ Practices and Expectations

Abstract: A research project to study e-book adoption in the humanities was conducted at the University of Illinois at Urbana-Champaign (UIUC).E -books are a topic of interest to librarians from all library types and all subject disciplines. Librarians at the University of Illinois at Urbana-Champaign (UIUC) have published studies on e-book use and value that specifically focused on science disciplines. Chrzastowski's 2011 study revealed that physical and life scientists used and benefited from early adoption of e-books… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, for many humanities scholars, particularly those working with large datasets or who conduct research in digital spaces, daily practices are changing. Although humanities scholars continue to value and use physical resources (e.g., Baruchson‐Arbib & Bronstein, ; Martin & Quan‐Haase, ; Rimmer, Warwick, Blandford, Gow, & Buchanan, ) and some scholars may prefer reading in print (e.g., Kachaluba, Brady, & Critten, ), e‐books are used by many humanities scholars (e.g., Chrzastowski & Wiley, ) and digital texts are an increasingly integral part of their scholarship (e.g., Borgman, ; Kachaluba et al, ). Despite their increasing importance, problems with digital texts may remain, such as issues with authority (Sinn & Soares, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, for many humanities scholars, particularly those working with large datasets or who conduct research in digital spaces, daily practices are changing. Although humanities scholars continue to value and use physical resources (e.g., Baruchson‐Arbib & Bronstein, ; Martin & Quan‐Haase, ; Rimmer, Warwick, Blandford, Gow, & Buchanan, ) and some scholars may prefer reading in print (e.g., Kachaluba, Brady, & Critten, ), e‐books are used by many humanities scholars (e.g., Chrzastowski & Wiley, ) and digital texts are an increasingly integral part of their scholarship (e.g., Borgman, ; Kachaluba et al, ). Despite their increasing importance, problems with digital texts may remain, such as issues with authority (Sinn & Soares, ).…”
Section: Introductionmentioning
confidence: 99%
“…11 However, Chrzastowski and Wiley emphasize that "uses" under this distinction, even if relatively brief, are still valuable for discovery or other tasks. 12 Thus they argue that the relatively high frequency of brief uses among humanists as compared to more immersive (reading) uses does not signal low value of e-books for this population. Related to user needs and tasks, D'Ambra, Wilson, and Akter have explored the task-technology fit (TTF) model in relation to e-book use, predicting academic task, technology characteristics, and individual characteristics will shape use of e-books and impact performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chrzastowski (2011) noted that the use of e-books is more profound in the physical and life sciences disciplines as compared to the use trends prevalent in the social sciences and humanities. Chrzastowski and Wiley (2015) reported that researchers in the humanities lagged behind researchers in other fields in the use of e-books, due to the different levels of reading required in the humanities disciplines. Staiger (2012) observed that users prefer print books for in-depth reading – referred to as immersive reading – while e-books are appropriate resources for retrieving specific and pinpointed information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sprague and Hunter (2008) noted that students in the disciplines of library sciences, economics and business are favourably inclined towards using e-books. Thus, e-book publishers try to tap the potential of e-book market for gaining maximum profit by tagging high price for e-books (Chrzastowski and Wiley, 2015). There is a good chance of availability of e-books in disciplines where e-books are preferred and demanded.…”
Section: Literature Reviewmentioning
confidence: 99%